PEMERIKSAAN SENGKETA TINDAKAN PEMERINTAHAN PASCA PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2019 - Sudarsono Sudarsono; Rabbenstain Izroiel (Universitas Islam Darul Ulum, 2022)
Examination of cases of unlawful acts by the government (onrechtmatige overheidsdaad) prior to the enactment of Law Number 30 of 2014 in conjunction with Supreme Court Regulation Number 2 of 2019 was carried out by the General Court. After the enactment of the Supreme Court Regulation Number 2 of 2019, the examination of the onrechtmatige overheidsdaad case was transferred to the TUN Court as a Government Action dispute. As a relatively new procedural law in the State Administrative Court, it is necessary to conduct legal research. This normative legal research found that the Government Action dispute is a public dispute whose examination must use the procedural law of the State Administrative Court, no longer using Article 1365 of the Civil Code. The object of the dispute is Government Action, either in the form of acts of action or non-action, carried out by government agencies and/or officials that cause harm to community members. This study resulted in suggestions for socialization and legal enforcement of the examination of disputes over Government Actions in order to realize legal and justice systems.